Complementary phenol‐enriched olive oil improves HDL characteristics in hypercholesterolemic subjects. A randomized, double‐blind, crossover, controlled trial. The VOHF study - Farràs, Marta; Castañer, Olga; Martín‐Peláez, Sandra; Hernáez, Álvaro; Schröder, Helmut; Subirana, Isaac; Muñoz‐Aguayo, Daniel; Gaixas, Sònia; Torre, Rafael de la; Farré, Magí; Rubió, Laura; Díaz, Óscar; et al. (Molecular nutrition & food research, 2015)
SCOPE: Consumption of olive oil (OO) phenolic compounds (PCs) has beneficial effects on lipid profile. HDL functionality is currently considered to be a more important issue than its circulating quantity. Our aim was to assess whether functional virgin olive oils (FVOOs), one enriched with its own PC (500 ppm; FVOO) and another with OOPC (250 ppm) plus additional complementary PCs from thyme (250 ppm) (total: 500 ppm; FVOOT (functional virgin olive oil with thyme)), could improve HDL functionality related properties versus a virgin OO control (80 ppm; VOO). METHODS AND RESULTS: In a randomized, double‐blind, crossover, controlled trial, 33 hypercholesterolemic volunteers received 25 mL/day of VOO, FVOO, and FVOOT during 3 wk. HDL cholesterol increased 5.74% (p < 0.05) versus its baseline after the FVOOT consumption in the participants without hypolipidemic medication. We detected, after FVOOT consumption, an increase in HDL₂‐subclass (34.45, SD = 6.38) versus VOO intake (32.73, SD = 6.71). An increment in esterified cholesterol/free cholesterol and phospholipids/free cholesterol in HDL was observed after FVOOT consumption (1.73, SD = 0.56; 5.44, SD = 1.39) compared with VOO intervention (1.53, SD = 0.35; 4.97, SD = 0.81) and FVOO intervention (1.50, SD = 0.33; 4.97, SD = 0.81). Accordingly, lecithin‐cholesterol acyltransferase mass increased after FVOOT consumption (1228 μg/mL, SD = 130), compared with VOO consumption (1160 μg/mL, SD = 144). An improvement in HDL oxidative‐status was reflected after FVOOT consumption versus its baseline, given an increment in the paraoxonase activity (118 × 10³ U/L, SD = 24). CONCLUSION: FVOOT improves HDL‐subclass distribution and composition, and metabolism/antioxidant enzyme activities. FVOOT could be a useful dietary tool in the management of high cardiovascular risk patients.